2010
DOI: 10.1111/j.1365-2982.2009.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-induced bowel disorders and narcotic bowel syndrome in patients with chronic non-cancer pain

Abstract: Bowel disorders including chronic abdominal pain and NBS are common in patients taking opioids for CNCP. Decreased HRQoL in patients with CNCP is driven by chronic abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
2
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 31 publications
6
96
2
6
Order By: Relevance
“…In the same study gastroesophageal reflux related symptoms were reported by 33% of all patients, nausea by 27% and vomiting by 9%. Furthermore, chronic abdominal pain was reported by 58% [Tuteja et al 2010]. Similar results have been found in a population-based survey along with increased frequency of constipation-related symptoms (including straining, hard stools, bloating and infrequent bowel movements) [Choung et al 2009].…”
Section: Prevalence Of Opioid-induced Bowel Dysfunctionsupporting
confidence: 73%
“…In the same study gastroesophageal reflux related symptoms were reported by 33% of all patients, nausea by 27% and vomiting by 9%. Furthermore, chronic abdominal pain was reported by 58% [Tuteja et al 2010]. Similar results have been found in a population-based survey along with increased frequency of constipation-related symptoms (including straining, hard stools, bloating and infrequent bowel movements) [Choung et al 2009].…”
Section: Prevalence Of Opioid-induced Bowel Dysfunctionsupporting
confidence: 73%
“…Clinical reports suggest that, of the several adverse effects of long-term opiate use, constipation is one of the most debilitating (Grond et al, 1994;Kurz and Sessler, 2003;Droney et al, 2008;Tuteja et al, 2010). Studies in several species, including the mouse and guinea pig, have demonstrated that morphine alters gastrointestinal motility and produces constipation via its effect on -opioid receptors (Roy et al, 1998;Sternini et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Side effects to morphine treatment include nausea and vomiting, abdominal pain, and constipation, which collectively are referred to as "opioid-induced bowel dysfunction." Although tolerance develops toward many of the effects of morphine, including analgesia, constipation remains resistant to tolerance such that in many cases patients choose to limit or discontinue opioid treatment (Moore and McQuay, 2005;Holzer et al, 2009;Tuteja et al, 2010). Consistent with the persistence of morphine-induced constipation in humans, tolerance to morphine-induced retardation of colonic transit does not develop in either moderate (5.5-fold) or high (52-fold) antinociceptive tolerance mice .…”
Section: Introductionmentioning
confidence: 99%
“…OIC can occur even at low dosages of opioids [Shook et al 1987] and can occur at any time after initiation of opioid therapy [Choi and Billings, 2002]. Nausea, vomiting and gastroesophageal reflux are the other symptoms associated with OIC [Tuteja et al 2010]. …”
Section: Clinical Presentation Of Oicmentioning
confidence: 99%